Antimicrobial activity and identification of secondary metabolites in summer oyster mushroom (Pleurotus ostreatus) extracts (Asian Journal of Agriculture, 2024)
Abstract. Devi NB, Kalpana CA. 2025. Antimicrobial activity and identification of secondary metabolites in summer oyster mushroom (Pleurotus ostreatus) extracts. Asian J Agric 9: 31-39. Consumption of oyster mushrooms is increasing due to their unique flavor, meaty taste, and extensive medicinal potential. The main aim of this study is to analyze and compare antimicrobial assays and identify secondary metabolites present after different drying techniques of oyster mushrooms. Oyster mushrooms were dried three different ways: Sun-Dried (SD), Cabinet-Dried (CD), and Freeze-Dried (FD). The dried samples were powdered and macerated using ethanol as a solvent extract and ultrasound treated. An antimicrobial assay was performed for the extracts using two Gram-positive and two Gram-negative bacteria. Gentamycin was used as a positive control and ethanol as a negative control. Further phytochemical screening was performed on the extracts to identify secondary metabolites, and other organic and inorganic compounds were identified by Fourier Transform Infrared Spectroscopy (FTIR) analysis. The study revealed that the mean zone of inhibition by SD, CD and FD oyster mushroom extracts against Staphylococcus aureus were 15.6 mm, 17.2 mm and 13 mm respectively while against Bacillus cereus were 0 mm, 0 mm and 14 mm respectively. And the mean zone of inhibition by SD, CD and FD oyster mushroom extracts against Escherichia were 12.6 mm, 7.8 mm and 15.4 mm respectively whereas against Pseudomonas aeruginosa were 1 mm, 0 mm and 11.4 mm respectively. The study also found that all three samples contained good amounts of alkaloids and carbohydrates, flavonoids, sterols, anthraquinones, and cardiac glycosides. All the samples showed bands in the IR regions of 400-4000 cm-1. The study concluded that the FD oyster mushroom preserved more secondary metabolites that had potential role in antimicrobial activity. The present work extends the finding of previous work by adopting ultrasonication as an extraction process, to compare the antimicrobial activity and identification of secondary metabolites of different drying method for summer-grown oyster mushroom cultivated in Coimbatore District of Tamil Nadu, India.
Keywords: Dhingri, FTIR, lyophilization, phytochemical, ultrasonication